Kant on Philosophy as Conceptual Analysis - Lewin, Michael (Con-Textos Kantianos. International Journal of Philosophy, 2023)
For Kant, philosophical investigations are inherently analytic. The proper method of philosophy is analysis, and the object of analysis are concepts. Hence, Kant’s short description of philosophy as “rational cognition […] from concepts” (KrV, A 837/B 865) can be substituted by “philosophy is conceptual analysis”. The article shows that Kant follows a representationalism about concepts and a combination of intensional and extensional feature semantics. Against the claim that Kant is a proponent of the concept-judgement-inversion, it is argued that concepts are being articulated in form of singular terms, propositions, and sets of propositions alike. Kant interlinks different kinds of concepts with different kinds of definitions, as the reconstruction of his theory of definitions reveals. Philosophy foremost deals with what Kant calls “given” empirical and pure concepts. Such concepts are object of analysis, i.e., explication and exposition. The article ends with answers to five possible objections. Is philosophy all about analysis?